Exploring gambling behavior and attitudes among college students in Iceland : a gender perspective - Ágúst Ármann 2001- (2023)
This thesis offers an exploration of the differences in gambling behaviors and attitudes that exist between female and male college students in Iceland. It is of increasing importance to spotlight this demographic given the escalation of the prevalence of gambling activities and exposure to gambling venues that have increased the risk of the progression of problem gambling. The variables that shape these behaviors will help us understand the possible implications for students' mental health and financial stability. The focus of this research was to examine how gender, personalities, social influences, and cultural norms play a role in shaping gambling habits among our population. The study results conclude that there is a noticeable gender gap in prevalence and attitudes toward gambling, with male students being more likely to engage in these behaviors and have an overall positive attitude toward gambling. Gambling among females was not specifically popular, and the opinions among female participants were overall negative. In conclusion, the results from this study emphasize the importance of implementing treatments to reduce problem gambling, with efforts being focused more on the male population than females. This work establishes the foundation for future research, and the findings highlight the need for gender-specific therapies order to encourage healthier mindsets and behaviors among college students concerning gambling.